1962
DOI: 10.1139/v62-306
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Carbon Monoxide and Carbon Dioxide Adsorbed on Chromia–alumina and on Alumina

Abstract: Infrared spectra of CO and CO:: adsorbed on chromia-alumina and on alumina surfaces have been determined. A band near 2200 cm-I formed by CO on both surfaces a t room temperature was due to a weak, non-activated sorption, but also contained a co~ltribution from a more strongly sorbed, activated species on the chro~nia-alurni~la. The assignment of this band was discussed in some detail. Bands in the region 1200-1800 c~n-' were co~lsiclered in terms of surface CO2-species, although in certain instances the appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 11 publications
(7 reference statements)
1
26
0
Order By: Relevance
“…Hence, it can be concluded that CO is retained on the catalyst in two forms: one form is liberated as CO2 only when the catalyst is fully oxidized (100% 02, 1 h, 773 K), whereas the other type is already liberated as CO2 when the catalyst is partly reoxidized (2.5% 02, 240s, 533-613 K). Based on literature, the first type is addressed to a carbonate species and the second type to CO adsorbed on coordinatively unsaturated surface (cus) Cr 3+ sites (Little and Amberg, 1962;Shelef et al, 1968;Burwell et al, 1969;Zecchina et al, 1969;Bijsterbosch et al, 1992). Assuming that each chromium atom present at the catalyst surface is occupied by one CO after complete reduction, the total amount of retained CO gives the Cr dispersion of the catalyst, i.e_ 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be concluded that CO is retained on the catalyst in two forms: one form is liberated as CO2 only when the catalyst is fully oxidized (100% 02, 1 h, 773 K), whereas the other type is already liberated as CO2 when the catalyst is partly reoxidized (2.5% 02, 240s, 533-613 K). Based on literature, the first type is addressed to a carbonate species and the second type to CO adsorbed on coordinatively unsaturated surface (cus) Cr 3+ sites (Little and Amberg, 1962;Shelef et al, 1968;Burwell et al, 1969;Zecchina et al, 1969;Bijsterbosch et al, 1992). Assuming that each chromium atom present at the catalyst surface is occupied by one CO after complete reduction, the total amount of retained CO gives the Cr dispersion of the catalyst, i.e_ 20%.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the physisorbed state of CO 2 , commonly described by a linear complex, leading to adsorption by an extremity, i.e., an oxygen [26]. Such adsorption minimizes the adsorbateadsorbate interactions, contrary to the fundamental assumption of this model.…”
Section: Fowler-guggenheim Equationmentioning
confidence: 90%
“…Further CO adsorption studies of mesoporous alumina have also focussed on CO removal, 65 while most studies have featured alumina for catalytic purposes. [66][67][68]…”
Section: Activated Aluminamentioning
confidence: 99%